Sensitivity analysis for automotive EMC measurements using quasistatic Darwin model. Issue 3 (16th December 2021) - Bingler, Arnold; Bilicz, Sándor; Csörnyei, Márk
Abstract : Purpose: The purpose of this paper is performing a global sensitivity analysis for automotive electromagnetic compatibility (EMC) measurements related to the CISPR 25 setup in order to examine the effect of the setup uncertainties on the resonance phenomenon. Design/methodology/approach: An integral equation formulation is combined with Darwin model and special Green's functions to model the configuration. The method of Sobol' indices is used to gain sensitivity factors enhanced with a polynomial chaos metamodel. Findings: The proposed model resulted in by orders of magnitude lower number of degrees of freedom and runtime compared to popular numerical methods, e.g. finite element method. The result of the sensitivity study is in good agreement with the underlying physical phenomena and improves the understanding of the resonances. Practical implications: The fast model supplemented by the sensitivity factors can be used in EMC design and optimization. Originality/value: The proposed method is original in the sense of combining a polynomial chaos metamodel with a low-cost integral equation model to reduce the computational demand for the sensitivity study.